The Correlation Between TOEFL Reading Score and Critical Reading Comprehension of EFL Students - Anggriyani, Resti; Ruslin, Ruslin; Dzakiah, Dzakiah; Syam, Hijrah (Universitas Muhammadiyah Mataram, 2025)
TOEFL has played a very important role in predicting students’ academic performance. However, very limited research has specifically addressed the relationship between the TOEFL reading section and students’ critical reading comprehension, as most existing studies predominantly focused on the correlation between overall TOEFL scores and students’ academic performance in general, such as GPA. This research examined the correlation between TOEFL reading score and critical reading comprehension of TBI students at UIN Datokarama Palu. A quantitative approach through correlational design was employed with 30 students as participants. Data were collected by using TOEFL reading test and GPA of critical reading comprehension course of students. Pearson product moment correlation was used to analyze the data. The results revealed a significant positive moderate correlation (r = 0.587, p = 0.01) between two variables. Reflecting that as one variable increases, the other variables tend to increase as well with a meaningful but not perfectly linear relationship. This indicates that students’ proficiency in the TOEFL reading section not only reflects their reading ability in English generally, but also correlates with their capacity to understand, analyze, interpret, and evaluate information in the reading text critically. By integrating TOEFL reading test into students’ critical reading exercises, educators can strengthen students’ critical reading comprehension that emphasizes determining main idea, identifying arguments, and evaluating evidences.